ANALISIS PENGARUH PAJAK HOTEL, PAJAK RESTORAN, DAN PAJAK PENERANGAN JALAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KERINCI - Dewi Ernita (Gapenas Publisher, 2021)
This study aims to determine: 1.) To determine the effect of Hotel Tax, Restaurant Tax, and Street Lighting Tax on the Regional Original Revenue of Kerinci Regency in Partial and Simultaneous. 2) To find out the effect of Hotel Tax, Restaurant Tax, and Street Lighting Tax on Kerinci Regency's Original Revenue Partially and Simultaneously.The data collected in this study are secondary data, namely Ho tel Tax, Restaurant Tax, Street Lighting Tax, and Kerinci Regency Original Income from 2010 to 2020. The data analysis tool used is Multiple Linear Regression Analysisased on the results of the study, it shows that 1) There is no significant effect bet ween Hotel Tax on Kerinci Regency's Original Revenue in 2010-2020. This is evidenced by • There is no significant effect of Hotel Tax on Kerinci Regency's Original Revenue in 2010 -2020. This is evidenced by the value of t arithmetic 1.087 < t table 2.365 o r a significance level of 0.313 > 0.05. There is no significant effect between Restaurant Tax on Kerinci Regency's Original Revenue in2010-2020. This is evidenced by the t arithmetic value of 1.872 < t table 2.365 or a significance level of 0.103 > 0.05. There is no significant effect between the Street Lighting Tax on the Kerinci Regency's Original Revenue in 2010-2020. This is evidenced by the t arithmetic value of 0.009 < t table 2.365 or a significance level of 0.993 > 0.05. There is a significant effe ct between Hotel Tax, Restaurant Tax and Street Lighting Tax on Kerinci Regency's Original Revenue in 2010 -2020. This is evidenced by the calculated F value of 7.513 > F table of 4.347 or a significance level of 0.014 <0.05. The Great Influence of Hotel Tax, Restaurant Tax, and Street Lighting Tax on Kerinci Regency'sOriginal Revenue 2010-2020. The effect of hotel tax (X1) on local revenue (Y) partially is 0.18%. The effect of restaurant tax (X2) on local revenue (Y) partially is 75.84%. The effect of str eet lighting tax (X3) on local revenue (Y) partially is 0.31%. The magnitude of the effect of Hotel Tax (X1), Restaurant Tax (X2), and Street Lighting Tax (X3) simultaneously on Local Revenue (Y) is 76.3% and the remaining 23.7% is influenced by other fact ors outside of this study